Functional Strength Training with Synchronized Method and Its Effect in Performing Some Gymnastic Skills among Women (Journal of the College of Basic Education, 2022)
This study aims to prepare training that includes planning and exercise for the functional strength in the synchronized method and identifying their effect in the performance of some skills of gymnasium among women. The researcher hypothesized that such s training has a positive effect in the progress of performance level for each of the skills of adduction jumping on the vault, groundbreaking on the vault, getting on the balance beam) among the female players of the College of Physical Education and Sport Science team. The researcher used the experimental design with two experimental groups. The study included a sample of 14 players who were purposively selected representing 100.0% of the target population (the female players of the College of Physical Education and Sport Science team) for the academic years 2019-2020 under the umbrella of the Iraqi Central Gymnasium Federation. After adopting the technical performance evaluation form to be evaluated by an expert panel, the exercises were applied for the first experimental group (functional strength training in the synchronous method), and the second experimental group (functional strength training) for eight training weeks at a rate of three sessions per week so that the focus in these exercises on developing the strength of muscles involved in directing the technical performance of the three skills. Data were analyzed using the statistical package for social science (SPSS), version 26. The study results revealed that applying the functional strength training in a synchronous manner in the period of special preparation helps gymnasts improve their performance for both adduction jumping on the vault, groundbreaking on the vault, getting on the balance beam at the local level. Continuing to train the functional strength during the special preparation period at the same pace improves the technical performance of these skills, but not to the level reached by the players who applied these exercises in a synchronous manner. This calls for the adoption of comprehensive training and limiting the exaggeration of the duration and intensity of the fixed weight training efforts being made to develop strength. Furthermore, it is necessary for the coaches to pay attention to the principle of progression and ripple in the training load according to the ability of each player on resistance training and their endurance without harming the kinetic programs of technical performance. So, this can to come in line with the long-term planning of their international professionalism in the future.